Genome resequencing and transcriptome analysis reveal the molecular mechanism of albinism in Cordyceps militaris - Zhao, Ying; Liu, YuDong; Chen, Xun; Xiao, Jun (Frontiers in Microbiology, 2023)
Light is an important regulator of most fungal life activities and transmits signals through certain photoreceptor proteins such as phytochromes and cryptochromes. However, the light response mechanism varies across different fungi. The WCC complex composed of white collar-1 (WC-1) and white collar-2 (WC-2) is considered to be the key factor regulating fungal albinism. The photoreceptor protein Vivid (VVD) is the negative regulator of the WCC complex. In this study, we discovered an albino mutant (Alb) generated by 60Co-γ-ray irradiation from Cordyceps militaris (C. militaris). This mutant showed albinism of the mycelia and fruiting bodies under light, and the fruiting bodies developed normally. However, this phenotype in Alb differed from that in the CmWC-1 mutant. This suggests that CmWC1 may not be mutated in Alb. A mutated polyketide synthase (CmPKS) was found through genome resequencing analysis. CmPKS was significantly induced by a light signal, and its mutation reduced melanin accumulation in C. militaris. In addition, we found that a zinc-finger domain-containing protein (CmWC-3) was induced by a light signal and interacted with CmWC-1 and CmVVD. Moreover, CmWC-2 also interacted with CmWC-1 to form the WCC complex and was inhibited by CmVVD. In addition, CmWC-3 directly bound with the CmPKS promoter, but CmWC1 did not. These results suggest that albinism and fruiting body development are two independent processes; the WCC complex of CmWC-1 with CmWC-3 regulates CmPKS expression to regulate color change, whereas CmWC-1 with CmWC-2 affects fruiting body development via the carotenoid pathway. These findings will help us to better understand the albinism mechanism of C. militaris.